Dynamics, temperature, chemistry, and dust: Ingredients for a self-consistent AGB wind. Issue Volume 14:Issue S343(2019) (August 2018) - Boulangier, J.; Gobrecht, D.; Decin, L.
Abstract: Understanding Asymptotic Giant Branch (AGB) stars is important as they play a vital role in the chemical life cycle of galaxies. AGB stars are in a phase of their life time where they have almost ran out of fuel and are losing vast amounts of material to their surroundings, via stellar winds. As this is an evolutionary phase of low mass stars, almost all stars go through this phase making them one of the main contributors to the chemical enrichment of galaxies. It is therefore important to understand what kind of material is being lost by these stars, and how much and how fast. This work summarises the steps we have taken towards developing a self-consistent AGB wind model. We improve on current models by firstly coupling chemical and hydrodynamical evolution, and secondly by upgrading the nucleation theory framework to investigate the creation of TiO2, SiO, MgO, and Al2O3 clusters.